Multigene phylogeny and morphology reveal a new species of Apiospora from the sclerotium of Papiliomyces longiclavatus - Chen, Hui; He, Yingzi; Tang, Dexiang; Wang, Yao (Phytotaxa, 2026)
A novel species, Apiospora papiliomyceticola sp. nov., is described from Guizhou Province, China. The species was isolated from the sclerotium of the cordycipitoid fungus Papiliomyces longiclavatus. Phylogenetic analyses based on a concatenated dataset of ITS, nrLSU, tef-1α, and tub2 sequences revealed that the new taxon forms a distinct lineage within Apiospora and is phylogenetically related to A. rasikravindrae, A. marinum, A. acutiapica, and A. pseudorasikravindrae. Morphologically, the species is characterized by globose to subglobose or ovate conidia and conidiogenous cells arising directly from hyphae, distinguishing it from related taxa. Detailed morphological comparisons with phylogenetically related species are provided. The integration of multigene phylogenetic analyses and morphological characteristics supports the recognition of A. papiliomyceticola as a distinct species.